The effect of welding speed variations on stainless steel – carbon steel fillet joints with the TIG welding method on the quality of the welded joint - Ahmad Naufal Syafiandika; Febri Budi Darsono; Muhammad Adi Inanto; Bayu Agung Nugroho; Muchamad Arya Ramadhan Nur Imam (Journal of Welding Technology, 2026)
Dissimilar welding between stainless steel and carbon steel is widely applied in industries such as power plants, petrochemical facilities, pressure vessels, and heat exchangers due to its ability to combine the advantages of both materials; however, studies investigating the effect of welding speed on TIG-welded fillet joints between ASTM A36 carbon steel and SS316 stainless steel remain limited, particularly regarding weld quality evaluation through non-destructive and destructive testing. This study aims to determine the effect of welding speed on the quality of TIG-welded fillet joints of ASTM A36 carbon steel and SS316 stainless steel. The welding process was performed using the Gas Tungsten Arc Welding (GTAW/TIG) method with ER309L filler metal and welding speed variations of 83, 86, and 93 mm/min in the 1F fillet position. Weld quality was evaluated through dye penetrant testing, radiography testing, and macrostructure examination to assess weld defects, fusion quality, and penetration characteristics. The results of dye penetrant testing indicated that specimens welded at 93 and 86 mm/min were free from surface defects, while the specimen welded at 83 mm/min exhibited a minor porosity defect of 0.5 mm. Radiography testing showed no internal defects, such as cracks, slag inclusions, lack of fusion, or lack of penetration, in all specimens. Macrostructural observations confirmed sound fusion between ASTM A36 and SS316 materials and revealed that welding speed significantly affected weld penetration. The deepest penetration was obtained at the lowest welding speed of 83 mm/min, reaching 1.25 mm, while penetration decreased with increasing welding speed. It can be concluded that all welding speed variations produced acceptable weld quality; however, a welding speed of 83 mm/min provided the best penetration performance due to higher heat input during the welding process.